Oxidized OxyR Up-Regulates ahpCF Expression to Suppress Plating Defects of oxyR- and Catalase-Deficient Strains - Wan, Fen; Yin, Jianhua; Sun, Weining; Gao, Haichun (Frontiers in Microbiology, 2019)
It is well established that in bacteria, such as Escherichia coli, OxyR is a transcriptional regulator that mediates the response to H2O2 by activating the OxyR regulon, which consists of many genes that play vital roles in oxidative stress resistance. In Shewanella, OxyR regulates, however in both reduced and oxidized states, the production of H2O2 scavengers, including major catalase KatB and NADH peroxidase AhpCF. Here we showed that the oxyR mutant carried a plating defect manifested as division arresting, a phenotype that can be completely suppressed by an OxyR variant constitutively existing in oxidized form (OxyRL197P). This effect of OxyRL197P could not be solely attributed to the increment in KatB production, since the suppression was also observed in the absence of KatB. Although expression of peroxidase CcpA was greatly activated by OxyRL197P, the contribution of the protein in alleviating plating defect was negligible. We eventually identified AhpCF as the critical factor, when produced at substantially elevated levels by OxyRL197P, to protect the cell from H2O2 attack. Our data indicate that AhpCF is a particularly important peroxidase in oxidative stress resistance in Shewanella, not only playing a compensatory role for catalase, but also by itself providing sufficient protection from killing of H2O2 generated abiotically.